Cellular delivery of pyrenyl-arene ruthenium complexes by a water-soluble arene ruthenium metalla-cage - Anca Furrer, Mona; Schmitt, Frederic; Wiederkehr, Michael; Juillerat-Jeanneret, Lucienne; Therrien, Bruno (My University, 2012)
Three pyrenyl-arene ruthenium complexes (M1-M3) of the general formula [Ru(?6-arene-pyrenyl)Cl2(pta)] (pta = 1,3,5-triaza-7-phosphaadamantane) have been synthesized and characterized. Prior to the coordination to ruthenium, pyrene was connected to the arene ligand via an alkane chain contg. different functional groups: ester (L1), ether (L2) and amide (L3), resp. Furthermore, the pyrenyl moieties of the Mn complexes were encapsulated within the hydrophobic cavity of the water sol. metalla-cage, [Ru6(?6-p-cymene)6(tpt)2(donq)3]6+ (tpt = 2,4,6-tri-(pyridin-4-yl)-1,3,5-triazine; donq = 5,8-dioxydo-1,4-naphthoquinonato), while the arene ruthenium end was pointing out of the cage, thus giving rise to the corresponding host-guest systems [Mn?Ru6(?6-p-cymene)6(tpt)2(donq)3]6+ ([Mn?cage]6+). The antitumor activity of the pyrenyl-arene ruthenium complexes (Mn) and the corresponding host-guest systems [Mn?cage][CF3SO3]6 were evaluated in vitro in different types of human cancer cell lines (A549, A2780, A2780cisR, Me300 and HeLa). Complex M2, which contains an ether group within the alkane chain, demonstrated at least a 10 times higher cytotoxicity than the ref. compd. [Ru(?6-p-cymene)Cl2(pta)] (RAPTA-C). All host-guest systems [Mn?cage]6+ showed good anticancer activity with IC50 values ranging from 2 to 8 ?M after 72h exposure. The fluorescence of the pyrenyl moiety allowed the monitoring of the cellular uptake and revealed an increase of uptake by a factor two of the M2 complex when encapsulated in the metalla-cage [Ru6(?6-p-cymene)6(tpt)2(donq)3]6+. [on SciFinder(R)]
Keywords: pyrenyl arene ruthenium triazaphosphaadamantane complex prepn anticancer activity reaction; triazaphosphaadamantane pyrenyl arene ruthenium metalla cage prepn anticancer activity